From similarity to conceptual—how pictophonetic Chinese characters facilitate inductive reasoning in 5–10-year-old children - Wang, Xiaoxi; Hu, Na; Ma, Ruimin; Cai, Xiaoying; Huang, Xuan (Frontiers in Psychology, 2025)
IntroductionInductive reasoning develops from similarity-based to category-based processes, and linguistic labels are thought to facilitate this shift, though whether they provide similarity or conceptual information remains debated.MethodsTo clarify the role of labels, we examined how Chinese children aged 5–10 interpret pictophonetic characters, focusing on semantic radicals that convey category information. Across three experiments, we manipulated cue strength (no, weak, strong) to test children’s inductive reasoning.ResultsChildren relied on phonetic radical similarity in the absence of cues but increasingly favored semantic radicals as cue strength intensified. Younger children tended to reason by perceptual similarity, whereas older children relied more on conceptual information, with evidence suggesting that ages 7–8 mark a developmental turning point.DiscussionThese findings indicate that orthographic awareness and literacy shape the transition from perceptual to conceptual reasoning, and that cue strength significantly influences semantic radical use. The study highlights the educational importance of supporting categorization skills and calls for further research on how character structures contribute to inductive categorization.